Practical business systems implementation : a DP guide - Varsegi, Alex. (New York : Van Nostrand Reinhold Company, Inc., 1988)
This book is written for professionals with previous exposure to data processing concepts in a main frame computer environment.
1. The requirements study -- 2. What to look for in an inhouse system -- 3. What to look for in a vendor package - Part I -- 4. What to look for in a vendor package - Part II -- 5. State of the art in vendor technology -- 6. Project status reporting -- 7. General or conceptual design -- 8. Detail design - part I -- 9. Detail design - Part II -- 10. On-line programming methods -- 11. Interface -- 12. Test environments and productivity tools - part I -- 13. Test environments and productivity tools - part II.
Includes index.
Keywords: BUSINESS -- DATA PROCESSING